Teste ergométrico em hipoxia: alternativa para avaliação cardiovascular de adultos e idosos - Freire, Jorge Luiz Palma (2016)
This investigation evaluated the electrocardiographic responses at rest and in the stress test of adults and elderly of both genres in normoxia and hypoxia situations. For this, were tested. 67 voluntaries from the ages of 50 to 79, divided in 45 sedentary persons, men and women (Group 1); 15 soccer players that play the city championship at the senior category (55 or plus) (Group 2) and seven high performance canoeists (Group 3). The participants were submitted, following the order, to rest and stress test EKG, in both normoxia and hypoxia situations. The EKG tracing results were compared qualitatively, between the described situations, and the clinical observations revealed in the tests analyzed. Results: 52 subjects presented EKG results of normal effort and without difference between the two test situations (normoxia and hypoxia). In 12 subjects were found tracing alterations that occur in hypoxia that didn t appeared in normoxia. Referring specifically to the hypoxia alteration, were shown, at total, a five-case occurrence of extrasystoles, eleven ST segment depression and 1 T wave flatness. The number of cases of apparently healthy persons, that didn t showed alteration of TEN and TEH, which allows to claim that the hypoxia exam is safe to these people. The cases of TEH alteration, without TEN correspondence, suggest that TEH can be more sensible to detect alterations with a possible pathological indicative; mainly referring to myocardial ischemia signals and rhythm disturbs.